Social cohesion, mutual efficacy and informal social control: Collective efficacy and community-based crime prevention - Gearhart, Michael C. (International journal of law, crime and justice, 2022)
Collective efficacy, which examines how social cohesion is activated in communities as informal social control, is a commonly used framework for community-based crime prevention. Previous research suggests that mutual efficacy, defined as group members’ perceptions that collective action can be successful, mediates the relationship between social cohesion and informal social control. However, previous research was limited in its measurement of mutual efficacy. The present study examines how mutual efficacy can facilitate participation in community-based crime prevention using a newly developed mutual efficacy scale. Findings suggest that social cohesion, mutual efficacy, and informal social control are distinct, though positively correlated constructs. Mutual efficacy partially mediates the relationship between social cohesion and informal social control. Findings suggest that building social cohesion and raising mutual efficacy are key goals for community-based crime prevention. Thus, practitioners should blend community practice principles with criminal justice goals to increase the effectiveness of interventions.